Redesain Panti Rehabilitasi Gangguan Jiwa Yayasan Al-Fajar Berseri Pendekatan Konsep Ekologi Kabupaten Bekasi - Idris, Samsul; Astuti , Retno Fitri; Miharti, Isria (Jurnal Pelita Teknologi, 2025)
Human health encompasses physical and mental well-being, where individuals can perform daily activities. However, with the rising cost of living, many face economic pressures and personal challenges. In Indonesia, approximately 17% of the population, or 42.5 million people, experience mental health issues. This includes patients at Yayasan Al-Fajar Berseri, where new patients continually outnumber those who recover. The rehabilitation center faces several issues, such as poor spatial circulation, small drainage systems prone to flooding, deteriorating inpatient facilities, lack of supporting amenities for healing, and disorganized parking areas. The project aims to redesign and replan the rehabilitation center by constructing humane inpatient housing to accommodate new patients and building essential facilities. The design approach integrates ecological principles, focusing on biological architecture that considers the psychological and architectural needs of the inhabitants. The center will feature green spaces, including vegetable and fruit gardens for food supply, fish ponds for aquaculture, livestock pens, and a craft workshop for productive activities. The layout will incorporate an arc-shaped building design inspired by traditional Tagog Anjing houses, creating a holistic environment that supports the patients' well-being. This design concept aims to provide a therapeutic and supportive environment for mental health recovery.